Nonsmooth H∞ synthesis of non-minimum-phase servo-systems with backlash. (January 2016) - Ponce, Israel U.; Orlov, Yury; Aguilar, Luis T.; Álvarez, Joaquín
Abstract: The nonsmooth phenomena such as backlash and Coulomb friction, often occurring in mechanical systems, typically produce undesired inaccuracies, oscillations and instability thereby degrading the system performance. The present paper addresses these phenomena in a benchmark two-mass system composed of motor and load subsystems joined by an elastic shaft. Only partial measurements of the motor position are assumed to be available. The H ∞ synthesis is then developed for a class of nonsmooth systems with backlash. The effectiveness of the proposed synthesis and its robustness features in the presence of friction forces and backlash effects are supported by an experimental study made for an industrial emulator.